1990
DOI: 10.1111/j.1365-2621.1990.tb01132.x
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and shelf‐life of a bottled pawpaw juice beverage

Abstract: Summary A simple procedure was developed for production of bottled pawpaw beverage juice by peeling and macerating peeled tissue in 25% water, straining through a 0.8‐mm sieve, adjustment of juice pH with citric acid and flavour adjustment with sucrose. Fresh juice was optimized for acceptability at pH 3.9 and 10% (w/w) sucrose. Heating for 6 min at 72.2°C was required to achieve commercial pasteurization. Samples of juice were prepared with no preservative, and containing sodium benzoate (125mg/100ml), sodium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…Tables 1-3 show that the effect of pasteurization time on the color, total solids, soluble solids, sugar, ascorbic acid, cloudiness, and browning index of beverages was less pronounced in the beverage preserved with sodium benzoate. Arya et al (1979) and Okoli and Ezenweke (1990) also reported similar results. Table 4 shows the microbial load during storage of spiced tamarind beverage produced by traditional processing method.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…Tables 1-3 show that the effect of pasteurization time on the color, total solids, soluble solids, sugar, ascorbic acid, cloudiness, and browning index of beverages was less pronounced in the beverage preserved with sodium benzoate. Arya et al (1979) and Okoli and Ezenweke (1990) also reported similar results. Table 4 shows the microbial load during storage of spiced tamarind beverage produced by traditional processing method.…”
Section: Resultssupporting
confidence: 64%
“…However, there was no significant change in the total acidity of the beverage up to 2 and 4 days of storage at room and refrigerated temperatures, respectively, while the pH changed significantly during the period. Paulson and Stevens ( 1974 ), Okoli and Ezenweke ( 1990 ) and Kamruzzaman et al. ( 2002 ) also observed that pH and acidity are not always inversely related.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Brix of the treatments was influenced significantly by the storage period where its mean decreased significantly from 13.8° at zero-time to 13.74° by the fifth month of storage. Such reduction in the TSS could be due to the microbiological activity in the drinks (Ekoli and Ezenweke, 1990).…”
Section: Physical and Chemical Characteristics Of Clear Apple Drinks mentioning
confidence: 99%